Doing translation history and writing a history of translation: the main issues and some examples concerning Portuguese culture. (2nd January 2016) - Seruya, Teresa
Abstract : Within Translation Studies, much research has been conducted under "the specific viewpoint [history] applied to the variety of material objects that share the label 'translation'". Moreover, the historical viewpoint responds to readers' expectations: be it a case study or a theoretical discussion, some historical background is demanded by accepted academic standards. It is part of a required context. However, a different issue emerges when the project of a history of translation in a particular country is to be reflected upon. My concern will be meta-historiographical in nature. Indeed, one of the main hurdles to be cleared is the use of some recurrent concepts in traditional historiography, such as "fact" and "event, " "change, " "progress" or "period." To what extent are they appropriate in translation history? Additionally, the narrative form implicit in history writing has to be tackled, as it implies a great deal of selection and exclusion, and above all questions of sequence and causation which are at the core of historical thought. The discussion of the above mentioned concepts will be illustrated with examples from Portuguese translation history.